(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
The automotive industry is crucial globally, but its increased use of fossil fuels poses environmental challenges. Linear economy vehicles emit more greenhouse gases, while circular economy aims to reduce pollution by redesigning processes and products. This paper explores the construction of an electric vehicle from an existing internal combustion engine, utilizing mechanics principles and fundamental engineering equations from mechanical and electrical analysis. The Toyota Starlet car was converted into an electric vehicle (EV) using four absorbed glass mat (AGM) lead acid batteries and a 48V direct current (DC) motor, with a 48V, 500Amps insulated-gate bipolar transistor (IGBT) electronic DC controller and a total capacity of 28.8KWh. It connects via a 5mm mild steel adapter plate and includes an electric booster vacuum pump. The donor vehicle’s steering and suspension systems were reused, along with various components like a 48V electric motor controller, charger, brake assist system, coupler, adapter plate, and electronic foot pedal. A 48V DC motor series wound was used, providing torque ranging from 102Nm to 115.8Nm for the EV’s wheel. The test resulted in an electric vehicle reaching a maximum speed range of 56-65KWh. Electric vehicles (EVs) offer simplicity, control, and cleanliness, potentially saving internal combustion engine (ICE) vehicles from extinction or scrapping and preventing global warming. The framework of this circular economy provides a solution for change across the lifecycle of a vehicle, providing the automotive industry a path towards a robust sustainable transportation solution.